Designing a Global Warming E-learning Module Using Adobe InDesign CS6 for Phase E Students - Pramasiwi, Handita; Fitri, Indah Karunia (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
The design and creation of an e-learning module on global warming using Adobe InDesign CS6 was driven by the need to balance and utilize the flow of digitalization in the world of education. The aim of this study was to: (1) describe the design and creation of a global warming e-learning module for phase E students using Adobe InDesign CS6, and (2) test the feasibility of a global warming e-learning module for phase E students using Adobe InDesign CS6. The global warming e-learning module based on Adobe InDesign CS6 was developed in three stages: preparation through problem identification, fabrication in the InDesign CS6 program, and completion with expert assessments. The validation data is analyzed using descriptive quantitative approaches to verify the module's practicality by comparing the total final scores using standard deviation and ideal mean methods. The analysis findings indicate that the designed global warming e-learning module is feasible in the media aspect with a score of 43, highly feasible in the material aspect with a score of 29, and also highly feasible in the linguistic component with a score of 25. Based on the findings, it is possible to conclude that: (1) an e-learning module with global warming material based on Adobe InDesign CS6 has been successfully created, and (2) the e-learning module on global warming that has been created is suitable for use in learning activities.